999 call-taker insights. (2nd July 2020) - Parry, Samuel
Abstract : As university lectures have moved online, Samuel Parry shares his experiences of becoming an emergency call-taker during the pandemic and his lessons learned about how 999 calls are dealt with before the crews on the road receive them